Reproductive success in the Lusitanian toadfish Halobatrachus didactylus: Influence of male and nest sizes - Carriço, Rita (2014)
Male reproductive success often depends on male attributes and resource quality. Here, we examined male preference for nest size in the Lusitanian toadfish, a nest-guarding fish with parental care.We also investigated the combined effect of male length and nest size in male breeding success. Approximately 80 shelters with five different sizes were placed on an intertidal zone of the Tagus estuary. Nests were checked every fortnight at spring low tides for occupation, nest-holder length, and number of eggs. Males did not select for the larger nests despite their availability but showed size assortative nest choice. Only nest size was a significant predictor of clutch size in occupied nests and it explained 60% of the variability in the number of obtained eggs. Male length and the interaction of male length and nest size did not have a significant effect on male reproductive success. These results suggest that although nest size is key to male's reproductive success, the choice for nest size results from a trade-off between accrued costs of offspring care or risk of a nest take-over and possible benefits of increased fitness.